Numerous retinal pigment epithelial elevations and drusen associated with unusual dilated choroidal vessels seen at choriocapillaris level in macular area - Akiko Okubo; Kazuhiko Unoki; Munefumi Sameshima; Taiji Sakamoto (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report the ocular findings in a patient with extensive diffuse elevations of the retinal pigment epithelium (RPE) and drusen associated with dilated choroidal vessels. Observations: The eye of a 72-year-old woman with numerous drusen and dilated choroidal vessels in the macular and surrounding areas of the right eye was studied. Her visual acuity was 20/16 in this eye and she was asymptomatic although the Amsler grid testing showed mild metamorphopsia. Indocyanine green angiography showed dilated choroidal vessels that collected blood from their branches in the macular and surrounding areas and flowed out of the eye at the entry site of a short posterior ciliary artery. A large choroidal vein ran from the nasal quadrants toward the superotemporal quadrant. Optical coherent tomography (OCT) showed two types of RPE elevations over an extensive area: one was a relatively steep dome-shaped RPE elevation, and the other was a flatter placoid-shaped RPE detachment. Detailed examinations including OCT angiography showed that the dome-shaped RPE elevation coincided with the course of the dilated choroidal vessels which were seen at the level of the choriocapillaris. The visual acuity and the ocular findings remained stable during the 2.5-year follow-up period, and this condition did not require any treatments. Conclusions and importance: We conclude that the dilated choroidal vessels are most likely parts of the posterior ciliary venous system, and they function as a posterior route of choroidal outflow. Because such eyes might be diagnosed and treated as age-related macular degeneration based on the presence of drusen, RPE detachments, and abnormal vessels beneath the RPE, knowledge of these observations in a functionally normal eye is important to avoid unnecessary treatments.